A multi-component intervention to reduce bias during family planning visits: qualitative insights on implementation from Burkina Faso, Pakistan and Tanzania - Corrina Moucheraud; Alexandra Wollum; Muhammad Ali Awan; William H. Dow; Willa Friedman; Jean-Louis Koulidiati; Amon Sabasaba; Manisha Shah; Zachary Wagner (BMC, 2024)
Abstract Beyond Bias was an intervention introduced in Burkina Faso, Pakistan and Tanzania, with the aim of reducing health worker bias toward young, unmarried and nulliparous women seeking family planning services. This study used qualitative methods - based on interviews with health workers who participated in the intervention, managers at health facilities that participated in the intervention, and policy and program stakeholders at the national level - to understand implementation experiences with the intervention. The results offer insights for organizations or countries seeking to implement Beyond Bias or similar programs, and point to some other key implementation challenges for multi-component interventions in lower-resource settings. The intervention, developed using a human-centered design approach, was seen as key for successful implementation but there were logistical challenges. The digital intervention was disruptive and distracting to many. In addition, the non-financial rewards intervention was perceived as complex, and some participants expressed feeling discouraged when they did not receive a reward. Beyond Bias did not sufficiently attend to the "outer setting," and this was perceived as a major implementation barrier as it limited individuals' capacity to fully achieve the desired behavior change; for example, space constraints meant that some health facilities could not ensure private services for all clients. There were scalability concerns related to cost, and there is uncertainty whether diversity of contexts (within and across countries) might constrain implementation of Beyond Bias at scale.